Positive electrode active material, secondary battery, and electric device
Patent Information
- Application Number
- CN202611224639.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-12
- Publication Date
- 2026-10-09
AI Technical Summary
[0003]然而,磷酸铁锂材料本身存在电子电导率低、锂离子扩散系数有限等本征缺陷
Smart Images

Figure CN122889727A_ABST
Abstract
Description
Technical Field
[0001] The exemplary embodiments of this application relate to the field of secondary batteries, and particularly to positive electrode active materials, secondary batteries, and electrical devices. Background Technology
[0002] With the rapid development of new energy vehicles, energy storage power stations, and portable electronic devices, increasingly higher requirements are being placed on the energy density, cycle life, and safety of lithium-ion secondary batteries. Among the many lithium-ion battery cathode materials, phosphate-based cathode active materials are widely used in power batteries and energy storage batteries due to their olivine crystal structure, flat charge and discharge platform, excellent thermal stability, abundant raw material sources, and relatively low cost.
[0003] However, lithium iron phosphate materials inherently suffer from low electronic conductivity and limited lithium-ion diffusion coefficient. In practical applications, especially under high-temperature conditions or in the presence of trace amounts of moisture in the electrolyte, the highly active iron compounds remaining on the surface of lithium iron phosphate particles are prone to oxidation and dissolution during charging and discharging. The dissolved iron ions migrate through the electrolyte to the negative electrode and are reduced and deposited, thereby catalyzing the reduction and decomposition of the electrolyte, accelerating the excessive growth of the solid electrolyte interphase (SEI) film, consuming active lithium, and blocking lithium-ion diffusion channels, ultimately leading to accelerated capacity decay and reduced cycle life. The deposited metallic iron may also form dendrites, posing safety hazards such as piercing the separator, causing internal short circuits, and thermal runaway. Summary of the Invention
[0004] In a first aspect of this application, a positive electrode active material is provided. The positive electrode active material includes active particles. The active particles include iron-based phosphate and a composite metal oxide, wherein the composite metal oxide contains a chemical formula of M... x Fe y O δ The compound, wherein M includes a metal element with an oxidation state greater than or equal to +2, 1≤x≤2, 1≤y≤2, 3≤δ≤6; the iron-based phosphate and the complex metal oxide are connected by POM covalent bonds.
[0005] In positive electrode active materials, the active particles are mainly composed of iron-based phosphates and composite metal oxides. From a microscopic mechanism perspective, the composite metal oxide M... x Fe y O δ It is generated during the sintering process by the in-situ reaction of metal oxides with highly reactive iron compounds (such as Fe2O3) remaining on the surface of iron-based phosphates under a weakly reducing atmosphere provided by a carbon source. Among them, the originally free metal cation M... n+POM covalent bonds are formed at the interface between the two phases by bridging oxygen (-O-) and phosphorus atoms in the phosphorus-oxygen tetrahedra (PO4) on the surface of iron-based phosphate. This covalent bond anchors the composite metal oxide to the surface of the iron-based phosphate particles through chemical bonding, so that the interface between the two is no longer a simple physical adhesion, but a chemically bonded interface with a continuous electron cloud.
[0006] Thus, the POM covalent bond provides a stable chemical anchoring effect between the composite metal oxide layer and the iron-based phosphate core: on the one hand, this chemical bond effectively consumes the highly chemically active iron-containing byproducts on the surface of the iron-based phosphate and transforms them into a chemically stable composite metal oxide structure, thereby significantly reducing the Fe²⁺ content on the cathode surface during cycling. + / Fe³ + On the one hand, the oxidation and dissolution probability is high; on the other hand, since electrons can migrate between the two phases along the conjugate path of the POM bond, there is no obvious electronic barrier between iron-based phosphate and composite metal oxide, thus constructing an efficient electron transport channel.
[0007] The chemical formula of the composite metal oxide, with 1≤x≤2, 1≤y≤2, and 3≤δ≤6, defines a reasonable stoichiometric relationship among the three elements M, Fe, and O. This stoichiometric relationship allows the composite metal oxide to exist in stable crystal forms commonly found in the field, such as spinel and perovskite, avoiding lattice distortion, vacancy enrichment, and structural instability caused by non-stoichiometric ratios. Simultaneously, within this ratio range, the composite metal oxide achieves a good balance between its "capture ability" of highly reactive iron compounds remaining on the surface of iron-based phosphates and its "impedement effect" on lithium-ion diffusion. While effectively suppressing iron dissolution, it does not significantly hinder the insertion / extraction migration of lithium ions on the particle surface due to an excessively dense oxide layer.
[0008] In some embodiments, the mass percentage of the composite metal oxide is 1 wt% to 5 wt%, based on the total mass of the active particles.
[0009] By controlling the mass percentage of composite metal oxides in the active particles within the range of 1wt% to 5wt%, iron dissolution can be suppressed while ensuring the full utilization of the material's energy storage performance. Maintaining the mass percentage of composite metal oxides within this range is sufficient to significantly reduce the number of iron dissolution active sites at the cathode / electrolyte interface, while simultaneously ensuring the dominant proportion of iron-based phosphates in the active particles.
[0010] In some embodiments, the mass percentage of the composite metal oxide can be one of 1 wt%, 2 wt%, 3 wt%, 4 wt%, and 5 wt%, or a range defined by any two of these values.
[0011] In some embodiments, M is selected from at least one of Al, Ti, Cr, Mn, Ga, Nb, Sn, Ta, and W.
[0012] The aforementioned metal elements all possess suitable ionic radii. Under their respective typical oxidation states and coordination states, the effective ionic radii of these metal elements match the sizes of the corresponding lattice sites in the composite metal oxides. Consequently, they can undergo solid-phase reactions with highly reactive iron compounds on the surface of iron-based phosphates under a weakly reducing atmosphere, and in the reaction products, they co-construct M with iron and oxygen elements in a stable oxidation state. x Fe y O δ Phase. From the perspective of ionic radius, Al 3+ Ti 4+ Cr 3+ Mn 3 + / Mn 4+ Ga 3+ 、Nb 5+ Sn 4+ Ta 5+ W 6+ Isocations can react with Fe 2+ / Fe 3+ They form size-matched oxygen octahedral or oxygen tetrahedral coordination structures, constituting dense lattices such as spinel or perovskite; from an electronic structure perspective, the M generated by the above elements x Fe y O δ Compounds (such as TiFeO3 and Cr2FeO4) exhibit narrow bandgap semiconductor or good conductor properties, showing a significant improvement in intrinsic electronic conductivity compared to iron-based phosphates. Therefore, the composite metal oxide layer can act as both a mechanical and chemical barrier to inhibit iron dissolution and as a high-conductivity channel to compensate for the poor electronic conductivity of iron-based phosphates.
[0013] In some embodiments, the M ion is in an oxygen-hexacoordinate state in the composite metal oxide, and the effective ionic radius of the M cation is 50 pm to 75 pm. The above effective ionic radius is related to Fe... 2+ and / or Fe 3+ The effective ionic radii are similar in the oxygen octahedral coordination state, which allows the M cation to occupy the metal cation sites in the iron oxide lattice or partially replace the Fe ions in the oxygen octahedral coordination state. This reduces the nucleation energy barrier of the composite metal oxide and improves the structural compactness and thermodynamic stability of the formed phase.
[0014] In some embodiments, the composite metal oxide includes at least one of the following compounds: Al2FeO4, TiFeO3, Cr2FeO4, MnFe2O4, Ga2FeO4, Nb2FeO6, SnFeO3, Ta2FeO6, and WFeO4.
[0015] The aforementioned compounds cover a wide range of typical phases, from spinel-type (such as Al2FeO4, Cr2FeO4, MnFe2O4, Ga2FeO4) to perovskite-type (such as TiFeO3, SnFeO3) and composite oxides constructed from higher valence metals (such as Nb2FeO6, Ta2FeO6, WFeO4). Their common characteristic is that the introduced metal element is stably coupled to the iron element in the same crystal lattice through a MO-Fe bridging structure in the molecular structure. From an electrical perspective, transition metal composite oxides such as TiFeO3, Cr2FeO4, and Mn(FeO2)2 often exhibit narrow band gaps, and their intrinsic electronic conductivity is significantly higher than that of iron-based phosphates, thus forming additional electronic conduction pathways in the in-situ coating layer. From a chemical stability perspective, main group metal composite oxides such as Al2FeO4 and Ga2FeO4 exhibit high chemical inertness, effectively resisting the corrosion of iron-based phosphates by acidic media in the electrolyte. Therefore, for different application scenarios, one or more of the above-mentioned specific compounds can be selected as composite metal oxides according to different requirements for conductivity and chemical stability.
[0016] In some embodiments, the crystal structure of the composite metal oxide includes at least one of a spinel-type structure and a perovskite-type structure.
[0017] The spinel-type structure has the general formula AB₂O₄, with oxygen ions arranged in a face-centered cubic close-packed configuration, and metal ions at the A and B sites occupying the interstices of tetrahedrons and octahedrons, respectively. The perovskite-type structure has the general formula ABO₃, with metal ions at the A-site occupying the vertices of the cube and metal ions at the B-site located at the center of the oxygen octahedron. In the composite metal oxide layer constructed by these two structures, iron ions can be stably locked in tetrahedral or octahedral crystal sites, further reducing the probability of iron ions escaping into the electrolyte under cycling conditions. Simultaneously, since both crystal structures are relatively common and highly stable phases in the field, they can withstand the chemical and electrochemical shocks of batteries under long-term cycling and high-temperature storage conditions, ensuring that the composite metal oxide layer maintains both structural and chemical stability throughout its service life.
[0018] In some embodiments, the iron-based phosphate comprises the chemical formula Li u Fe 1-a D aPO4, wherein 0.9≤u<1.1, 0≤a<1, and D is selected from at least one of Mn, Mg, Ti, V, Cr, Co, Ni, Cu, Zn, Al, Zr, and Nb.
[0019] In some embodiments, the positive electrode active material further includes carbon material disposed on the outside of the active particles, and the mass percentage of the carbon material is 1wt% to 2.5wt% based on the total mass of the active particles.
[0020] The outer carbon material coats the active particles, forming a multi-layered composite structure of iron-based phosphate, composite metal oxide, and carbon material. This allows for the creation of a three-dimensional conductive network between the active particles, enabling electrons to be transferred at multiple levels between the core, shell, and carbon network, thus synergistically improving the overall electronic conductivity of the positive electrode active material.
[0021] By controlling the mass percentage of the outer carbon material to be between 1 wt% and 2.5 wt%, a continuous three-dimensional conductive network can be constructed between the particles, compensating for the low electronic conductivity of iron-based phosphates. This also avoids the decrease in compaction density and loss of electrode volumetric energy density caused by excessive carbon content. Within this range, the carbon material can synergistically interact with the composite metal oxide layer connected by POM covalent bonds, forming a multi-level electronic pathway of "core electron transport → interface covalent bond transition → composite oxide layer → outer carbon network," thereby significantly improving the rate performance of the secondary battery without significantly sacrificing its energy density.
[0022] In some embodiments, the mass percentage of carbon material may be one of 1 wt%, 1.5 wt%, 2 wt%, and 2.5 wt%, or a range defined by any two of these values.
[0023] In some embodiments, the composite metal oxide is at least partially disposed on the outside of the iron-based phosphate, and the carbon material is at least partially disposed on the outside of the composite metal oxide.
[0024] By sequentially placing a composite metal oxide layer and a carbon layer on the outside of an iron-based phosphate, a multi-layered coating structure of "iron-based phosphate core - composite metal oxide intermediate layer - carbon material outer layer" can be constructed at the particle scale. In this structure, the composite metal oxide layer, as the inner coating layer, mainly functions as a "chemical barrier," anchoring itself to the surface of the iron-based phosphate through POM covalent bonds and consuming the highly active iron compounds remaining on its surface. The outer carbon material mainly functions as an "electronic conductivity network," forming a three-dimensional conductive framework through bridging between particles, further improving the overall electronic conductivity of the active material layer. Simultaneously, since the composite metal oxide layer and the iron-based phosphate are connected by POM covalent bonds, it is not a completely uniform continuous film; some areas may be discontinuous "island" coverages. The outer carbon material can directly contact the iron-based phosphate core in these discontinuous areas, thus ensuring the inhibition of iron dissolution while avoiding excessive blockage of lithium-ion diffusion channels by a completely dense oxide layer.
[0025] In some embodiments, the composite metal oxide is disposed on the outer side of the iron-based phosphate with a thickness of 5 to 50 nm.
[0026] The thickness of the composite metal oxide layer directly affects the balance between the chemical barrier effect and the lithium-ion diffusion resistance. Within the thickness range of 5–50 nm, the composite metal oxide layer can achieve partial coverage of the particle surface while providing limited but acceptable diffusion channels for lithium ions through its internal POM covalent bond pathways and some lattice defects, thus achieving the optimal balance between suppressing iron dissolution and maintaining high rate capability.
[0027] In some embodiments, the thickness of the composite metal oxide can be a value defined by one or any two of the following: 5 nm, 10 nm, 15 nm, 20 nm, 25 nm, 30 nm, 35 nm, 40 nm, 45 nm, and 50 nm.
[0028] In some embodiments, the thickness of the carbon material is set to 8~40 nm.
[0029] The thickness of the outer carbon material also significantly affects the electronic conductivity and volumetric energy density of the secondary battery. With a carbon layer thickness in the range of 8–40 nm, the carbon material can form continuous conductive pathways on the particle surface and in the interparticle spaces. Together with the composite metal oxide layer located inside it, it constructs a three-level electron transport path of "POM covalent bond-composite metal oxide-carbon network", which comprehensively improves the secondary battery in terms of multiple indicators such as cycle life, rate capability, and energy density.
[0030] In some embodiments, the thickness of the carbon material can be a value or a range defined by any two of the following: 15 nm, 20 nm, 25 nm, 30 nm, 35 nm, 40 nm, 45 nm, and 50 nm.
[0031] In some embodiments, the median particle size Dv50 of the positive electrode active material is 0.2 μm to 2 μm. In some embodiments, the median particle size of the positive electrode active material may be a value defined by one or any two of the following: 0.2 μm, 0.4 μm, 0.6 μm, 0.8 μm, 1.0 μm, 1.2 μm, 1.4 μm, 1.6 μm, 1.8 μm, and 2.0 μm.
[0032] In a second aspect of this application, a secondary battery is provided. The secondary battery includes a positive electrode sheet, the positive electrode sheet includes a positive current collector and an active material layer disposed on at least one surface of the positive current collector, the active material layer including the positive active material provided in the first aspect of this application.
[0033] In some embodiments, during the cycle test of the secondary battery at an ambient temperature of 25°C and a voltage range of 2.5~3.65V with 1C constant current and constant voltage charging / 1C constant current discharging, the iron migration amount of the positive electrode active material after 2000 cycles is less than or equal to 1000ppm, where the iron migration amount is the ratio of the iron mass on the negative electrode to the mass of the positive electrode active material.
[0034] In some embodiments, the amount of iron migration of the positive electrode active material can be a range defined by one or any two of the following values: 30ppm, 50ppm, 100ppm, 200ppm, 300ppm, 400ppm, 500ppm, 600ppm, 700ppm, 800ppm, 900ppm, and 1000ppm.
[0035] Because iron ions from the lithium iron phosphate cathode migrate to the anode under the influence of an electric field after dissolution, the amount of iron ions migrates from the cathode to the anode. The iron migration amount (ppm, mg / kg) of the cathode material can be calculated based on the ratio of the mass of iron in the anode to the mass of the cathode active material. The iron migration amount of the cathode active material directly reflects the amount of Fe ions on the surface of the iron-based phosphate particles under cycling conditions. 2+ / Fe 3+ The total amount of iron that migrates to the negative electrode through the electrolyte. When a stable composite metal oxide layer is formed on the particle surface through POM covalent bonds, the corrosion-induced iron dissolution caused by trace amounts of acidic media such as HF can be significantly suppressed, while the oxidative dissolution kinetic rate of iron under electric field polarization conditions is reduced.
[0036] Limiting the iron migration of the positive electrode active material to less than or equal to 1000 ppm after 2000 cycles ensures that the amount of metallic iron deposited on the negative electrode side is at a low level, avoiding the risk of membrane puncture and short circuit caused by iron dendrite growth, and avoiding excessive growth of SEI film and consumption of active lithium due to iron deposition, thereby significantly extending the cycle life of the secondary battery.
[0037] In some embodiments, the secondary battery further includes a negative electrode sheet. The negative electrode sheet includes a negative current collector and a negative active material layer. The negative active material layer includes a negative active material, which includes at least one of hard carbon, soft carbon, graphite, nitrogen-doped carbon material, and porous carbon material.
[0038] In some embodiments, the secondary battery further includes an electrolyte. The electrolyte can be an organic or inorganic solution with a lithium salt as the solute. For example, dehydrated lithium hexafluorophosphate can be dissolved in a carbonate solvent. The carbonate solvent may include at least one of ethylene carbonate (EC), propylene carbonate (PC), dimethyl carbonate (DMC), diethyl carbonate (DEC), and ethyl methyl carbonate (EMC).
[0039] In some embodiments, the secondary battery also includes an outer packaging, which can be rigid packaging, such as a hard plastic shell, aluminum shell, steel shell, etc. The outer packaging of the secondary battery can also be flexible packaging, such as a pouch-type soft pack, and the material of the soft pack can be polypropylene, polybutylene terephthalate, and / or polybutylene succinate.
[0040] In some embodiments, the secondary battery may be constrained by its outer packaging into any suitable shape. For example, the secondary battery as a whole may be cylindrical, prismatic, or other regular or irregular shapes to match the battery space of the electrical device.
[0041] In a third aspect of this application, an electrical device is provided. The electrical device includes a secondary battery according to any embodiment of the second aspect of this application, the secondary battery serving as a power supply for the electrical device.
[0042] Because the secondary battery used in this electrical device employs the aforementioned positive electrode active material with POM covalent bonds, it exhibits lower iron migration, higher capacity retention, and superior safety performance during long-term cycling. Based on this, the electrical device can simultaneously achieve improvements in service life, range, and safety redundancy under high-temperature conditions.
[0043] In some embodiments, the electrical equipment can be application devices such as vehicles, mobile phones, portable devices, laptops, ships, spacecraft, electric toys, and power tools. Vehicles can be new energy vehicles, including pure electric vehicles, hybrid electric vehicles, or range-extended electric vehicles; spacecraft include airplanes, rockets, space shuttles, and spacecraft; electric toys include stationary or mobile electric toys, such as game consoles, electric car toys, electric ship toys, and electric airplane toys; power tools include metal cutting power tools, grinding power tools, assembly power tools, and railway power tools, such as electric drills, electric grinders, electric wrenches, electric screwdrivers, electric hammers, impact drills, concrete vibrators, and electric planers. This application does not impose special limitations on the above-mentioned devices.
[0044] It should be understood that the content described in this section is not intended to limit the key or essential features of the embodiments of this application, nor is it intended to restrict the scope of this application. Other features of this application will become readily apparent from the following description. Attached Figure Description
[0045] The above and other features, advantages, and aspects of the embodiments of this application will become more apparent from the accompanying drawings and the following detailed description. In the drawings, the same or similar reference numerals denote the same or similar elements, wherein: Figure 1 A schematic diagram of the structure of active particles in the positive electrode active material of a secondary battery according to some embodiments of this application is shown; Figure 2 TEM images of the active particles of the positive electrode active material of a secondary battery according to some embodiments of this application are shown; and Figure 3 The XRD patterns of LiFePO4 composite materials loaded with TiFeO3 nanoparticles according to some embodiments of this application are shown. Detailed Implementation
[0046] Embodiments of this application will now be described in more detail with reference to the accompanying drawings. While embodiments of this application are shown in the drawings, it should be understood that this application may be implemented in various forms and should not be limited to the embodiments set forth herein. Rather, these embodiments are provided to make this application more thorough and complete, and to fully convey the scope of this application to those skilled in the art.
[0047] In the description of embodiments of this application, the term "comprising" and similar terms should be understood as open-ended inclusion, i.e., "including but not limited to". The term "based on" should be understood as "at least partially based on". The term "one embodiment" or "the embodiment" should be understood as "at least one embodiment". The term "some embodiments" should be understood as "at least some embodiments". Other explicit and implicit definitions may also be included below. The terms "first", "second", etc., may refer to different or the same objects. Other explicit and implicit definitions may also be included below.
[0048] In the field of lithium-ion secondary batteries, lithium iron phosphate (LFP) possesses outstanding advantages as a cathode active material, including high theoretical specific capacity, a flat charge-discharge plateau, excellent thermal stability, and long cycle life, making it a crucial cathode material for both power and energy storage batteries. However, several significant technical bottlenecks still exist in its practical engineering applications.
[0049] First, lithium iron phosphate (LFP) has low intrinsic electronic conductivity. Simply adding a carbon layer to the particle surface is insufficient to create a sufficiently comprehensive and interconnected electronic conduction network, thus limiting the capacity of the secondary battery under high-rate operating conditions. Second, during long-term cycling, especially under high-temperature conditions or when trace amounts of moisture are present in the electrolyte, highly corrosive media such as HF may be generated. This causes oxidation and dissolution of the highly active iron compounds remaining on the surface of the LFP particles. The dissolved iron ions migrate through the electrolyte to the negative electrode and are reduced and deposited as metallic iron. This catalyzes the reduction and decomposition of the electrolyte, accelerates the excessive growth of the SEI film, consumes active lithium, and blocks lithium-ion diffusion channels, ultimately leading to accelerated capacity decay and reduced cycle life. Furthermore, the metallic iron deposited at the negative electrode may continue to grow and form dendrites, posing a safety risk of piercing the separator, causing internal short circuits, exacerbating self-discharge, and even inducing thermal runaway.
[0050] Therefore, this application provides a secondary battery and an electrical device including the secondary battery. In this secondary battery, the positive electrode active material adopts a multi-layer structure of "iron-based phosphate core—composite metal oxide intermediate layer—carbon material outer layer". The chemical formula of the composite metal oxide is M... x Fe y O δ(1≤x≤2, 1≤y≤2, 3≤δ≤6), the composite metal oxide is connected to the surface of the iron-based phosphate through POM covalent bonds; carbon material is further disposed on the outside of the iron-based phosphate and the composite metal oxide, thereby establishing a three-dimensional conductive network between the active particles. This structure transforms the originally free, highly active iron compound into a stable composite metal oxide phase in situ through chemical bonding, which can simultaneously achieve chemical shielding against iron dissolution, multi-level synergistic improvement of electronic conductivity, and effective resistance to electrolyte corrosion. It can be achieved in conventional lithium-ion battery sintering processes through single sintering, double sintering, or multiple sintering, with a simple process route and controllable cost.
[0051] Figure 1 A schematic diagram of the structure of active particles in the positive electrode active material of a secondary battery according to some embodiments of this application is shown. Figure 2 TEM images of active particles prepared according to some embodiments of this application (i.e., Example 1 described below) are shown. (Refer to...) Figure 1 and Figure 2 The active particles consist of iron-based phosphate (e.g., LiFePO4 particles) located in the core and composite metal oxides (M...) disposed on the outside of the iron-based phosphate. x Fe y O δ It consists of a composite metal oxide and a carbon material layer partially covering the outside of the composite metal oxide. The composite metal oxide can be distributed discontinuously in an island-like pattern on the surface of the iron-based phosphate, which is partly due to the uneven distribution of the highly active iron compounds remaining on the surface of the iron-based phosphate particles. The outer carbon material further coats the active particles and forms continuous conductive bridges between them. Figure 2 A dense M layer with a thickness of about 20nm can be seen in it. x Fe y O δ The coating layer tightly covers the surface of the LiFePO4 particles.
[0052] The present application will be further described below with reference to specific embodiments. Where specific techniques or conditions are not specified in the embodiments, they shall be performed in accordance with the techniques or conditions described in the literature in this field or in accordance with the product instructions; where the manufacturers of reagents or instruments are not specified, they are all conventional products.
[0053] Example 1 Preparation of positive electrode active materials.
[0054] Preparation of precursor: Lithium carbonate, ferrous oxalate, and ammonium dihydrogen phosphate were weighed according to a Li:Fe:P molar ratio of 1.02:1:1. Then, 1 wt% of titanium dioxide (TiO2) and 4.0 wt% of sucrose (carbon source) were added. Anhydrous ethanol was used as the dispersion medium, and the mixture was ball-milled at 400 rpm for 6 hours in a planetary ball mill. The slurry obtained by ball milling was dried at 80°C for 12 hours to obtain dried precursor powder.
[0055] First sintering: The precursor powder is placed in an atmosphere sintering furnace and heated to 350°C at a heating rate of 5°C / min under the protection of high-purity nitrogen and held for 3 hours; then heated to 790°C at a heating rate of 3°C / min and held for 10 hours; after cooling in the furnace, it is ground and passed through a 400-mesh sieve to obtain a positive electrode active material in which carbon and composite metal oxide (TiFeO3) are synergistically coated on the outside of iron-based phosphate.
[0056] Figure 3 The XRD pattern of the LiFePO4 active material loaded with TiFeO3 nanoparticles prepared according to Example 1 of this application is shown. (Refer to...) Figure 3 The XRD pattern of the composite material shows an additional impurity peak at 2θ = 33.1°. Figure 3 (Marked with a ▼), the diffraction peak matches the peak position of TiFeO3, indicating that a TiFeO3 crystalline phase has formed in the obtained positive electrode active material. Combined with... Figure 2 The TEM image of the positive electrode active material shown confirms that the composite metal oxide TiFeO3 has been generated on the surface of the iron-based phosphate particles.
[0057] Preparation of the positive electrode sheet.
[0058] The positive electrode current collector is a carbon-coated aluminum foil with a thickness of 12 μm. The aluminum foil is carbon-coated on both sides, with a carbon layer thickness of 1 μm on each side.
[0059] A positive electrode slurry was prepared by mixing positive electrode active material, conductive agent Super P, and binder polyvinylidene fluoride (PVDF) in an N-methylpyrrolidone (NMP) solvent at a mass ratio of 96.5:2.0:1.5 under high-speed shearing. The solid content of the positive electrode slurry was 66%. A transfer coating machine was used to uniformly coat the two surfaces of the positive electrode current collector with the positive electrode slurry, with a coating weight of 254 mg / 1540 mm². 2 After segmented drying, the electrode compaction density is controlled to 2.6 g / cm³ by a precision roller mill; finally, the electrode is punched into the specified size to obtain the positive electrode.
[0060] Preparation of negative electrode sheet Negative current collector The negative electrode current collector is made of copper foil with a thickness of 6μm.
[0061] Artificial graphite (AG), Super P, sodium carboxymethyl cellulose (CMC), and styrene-butadiene rubber (SBR) were mixed and dispersed in deionized water at a mass ratio of 96.0:1.5:1.2:1.3 to prepare a negative electrode slurry with a solid content of 50.5%. The negative electrode slurry was then precision coated onto both surfaces of the negative electrode current collector, with a double-sided coating weight of 0.157 mg / mm². 2 After drying and rolling, the compacted density of the electrode sheets was controlled to be 1.62 g / cm³. 3 Then it is punched into the specified size to obtain the negative electrode sheet.
[0062] The capacity ratio (N / P) of the negative electrode to the positive electrode is 1.1. Electrolyte preparation In a high-purity argon glove box with a water content of less than 0.5 ppm and an oxygen content of less than 0.5 ppm, lithium hexafluorophosphate (LiPF6) was dissolved in a mixed solvent composed of ethylene carbonate (EC), dimethyl carbonate (DMC), and ethyl methyl carbonate (EMC) in a volume ratio of 1:1:1 to prepare a basic electrolyte with a concentration of 1.0 mol / L. Subsequently, 1 wt% of vinylene carbonate (VC) and 1 wt% of fluoroethylene carbonate (FEC) relative to the total mass of the electrolyte were added and stirred until completely homogeneous to obtain the electrolyte used for the secondary battery.
[0063] The positive electrode, porous polyethylene (PE) separator, and negative electrode are sequentially stacked and assembled to obtain a bare cell. The bare cell is placed in an aluminum-plastic encapsulation shell and vacuum baked at 85°C for 48 hours to fully remove moisture. Liquid injection and vacuum heat sealing are completed in a glove box. After the cell is allowed to stand and soak, it undergoes formation (0.02C constant current charging to 3.5V) and capacity testing (0.5C constant current-constant voltage charging to 3.65V, and then 0.5C constant current discharging to 2.5V) processes to finally obtain a secondary battery with a rated capacity of 2Ah.
[0064] Examples 2-9 The difference between Examples 2-9 and Example 1 is that, in the preparation of the precursor, titanium dioxide (TiO2), which is a metal oxide, is replaced by other metal oxides by mass. Specifically, the metal oxides used in Examples 2-9 are Al2O3, Cr2O3, MnO2, Ga2O3, Nb2O5, SnO2, Ta2O5, and WO3, respectively, which generate composite metal oxides Al2FeO4, Cr2FeO4, Mn(FeO2)2, Ga2FeO4, Nb2FeO6, SnFeO3, Ta2FeO6, and WFeO4 in situ on the surface of iron-based phosphate particles.
[0065] Examples 10-15 The difference between Examples 10-15 and Example 1 is that the amount of titanium dioxide (TiO2), a metal oxide, added is different in the preparation of the precursor.
[0066] Examples 16-17 The difference between Examples 16 and 17 and Example 1 is that the amount of sucrose added as a carbon source is different in the preparation of the precursor.
[0067] Comparative Example 1 The difference between Comparative Example 1 and Example 1 is that no metal oxide is added.
[0068] Comparative Example 2 The difference between Comparative Example 2 and Example 1 is that: no titanium dioxide is added during the precursor preparation process; after the precursor powder completes one sintering treatment, TiFeO3 particles are incorporated into the sintering product. The molar amount of Ti in the incorporated TiFeO3 is consistent with the molar amount of Ti in the titanium dioxide added in Example 1. After thorough mixing at room temperature, the positive electrode active material is obtained. The obtained positive electrode active material does not contain PO-Ti covalent bonds.
[0069] Examples 1-17 and Comparative Examples 1-2 are shown in Table 1.
[0070] Table 1
[0071] Note: In Table 1, " / " indicates that the item has not been added or is not involved.
[0072] Performance testing 1) Verification of POM covalent bonds X-ray photoelectron spectroscopy (XPS) was used to detect the positive electrode active material obtained in Example 1, with Comparative Example 1 (LiFePO4 / C material without TiO2) and Comparative Example 2 (a physical mixture of LiFePO4 / C and FeTiO3 at room temperature) used as comparative samples. High-resolution P 2p, O 1s, and Ti 2p spectra of each sample were acquired and corrected, and peak fitting was performed. Compared to Comparative Example 1 and Comparative Example 2, the O 1s spectrum of the positive electrode active material in Example 1 showed new interfacial oxidation state components, while the P 2p and Ti 2p spectra exhibited corresponding changes in binding energy, and these changes could not be simply obtained by superimposing the XPS spectra of LiFePO4 and FeTiO3. These results indicate that a PO-Ti chemical bond was formed between LiFePO4 and FeTiO3 in Example 1, and a PO-Ti chemical bond was formed between LiFePO4 and FeTiO3 in Comparative Example 2.
[0073] 2) Characterization of composite metal oxides in positive electrode active materials.
[0074] Phase analysis of the positive electrode active material was performed using X-ray diffraction (XRD) with a scanning range of 10°–70° and a scanning rate of 10° / min, using a CuKα radiation source. The presence of composite metal oxides (M) was determined by comparing the material with standard cards. x Fe y O δ The characteristic diffraction peaks are used to determine whether the composite metal oxide has been successfully generated in situ. The integrated area of the corresponding characteristic peak is read and substituted into the standard curve to calculate the relative content of the composite metal oxide in the composite material.
[0075] 3) The thickness of the composite metal oxide and carbon materials.
[0076] The morphology and interface of the positive electrode active material were analyzed using transmission electron microscopy (TEM). Multiple regions were randomly selected at the particle edges to measure the thickness of the composite metal oxide layer and the outer carbon layer, and the average value was taken. At least five different regions were measured in each sample to ensure data representativeness. The instrument accelerating voltage ranged from 20 kN to 200 kN.
[0077] 4) The carbon content in the positive electrode active material The carbon content in materials was determined using a high-frequency induction combustion-infrared absorption method. The sample was placed in a high-frequency induction furnace and heated to 1000℃–1300℃ in an oxygen atmosphere to completely convert carbon into carbon dioxide gas. The generated carbon dioxide was carried into an infrared detection cell by oxygen, and its characteristic absorption intensity was measured. The mass fraction of carbon was calculated using an external standard calibration curve (using a standard substance with known carbon content). Each sample was measured in triplicate, and the arithmetic mean was taken as the final result, with blank correction performed simultaneously.
[0078] 5) Discharge capacity of the secondary battery at 0.33C.
[0079] The prepared secondary battery was charged to 3.65V at a constant current and constant voltage of 0.33C at an ambient temperature of 25℃, with a cutoff current of 0.05C. After standing for 5 minutes, it was discharged to 2.5V at a constant current of 0.33C, and its discharge capacity was recorded. This indicator is used to evaluate the capacity performance of the modified lithium iron phosphate material at low rates, so as to avoid excessive dilution effect on the specific capacity due to the introduction of composite metal oxides.
[0080] 6) Capacity retention rate after 2000 cycles.
[0081] The prepared secondary battery was subjected to cyclic testing at an ambient temperature of 25℃ using a constant current and constant voltage charging method of 1C (cutoff current 0.05C) / constant current discharging method within a voltage range of 2.5~3.65V, for a total of 2000 cycles. The cycle capacity retention rate was calculated using the following formula: Cycle capacity retention rate = 2000th discharge capacity / 1st discharge capacity × 100%.
[0082] 7) Iron migration amount after 2000 cycles.
[0083] After 2000 cycles, the secondary battery was charged to 3.65V and then disassembled to remove the negative electrode. The negative electrode was ultrasonically treated with a strong acid solution to extract the deposited metal ions. Subsequently, inductively coupled plasma optical emission spectrometry (ICP-OES) was used to quantitatively analyze the iron (Fe) mass concentration in the extract, and the mass of iron generated on the negative electrode was further calculated.
[0084] Because iron ions from the lithium iron phosphate cathode migrate to the anode under the influence of an electric field after dissolution, they form iron on the graphite of the anode. The amount of iron migration in the cathode material (ppm, mg / kg) can be calculated based on the ratio of the mass of iron to the mass of the cathode active material.
[0085] The performance test data of Examples 1-17 and Comparative Examples 1-2 are shown in Tables 2 and 3.
[0086] Table 2
[0087] Note: In Table 2, " / " indicates that the item was not detected or was not found.
[0088] Table 3
[0089] The performance test results of Examples 1-17 and Comparative Examples 1-2 are shown in Tables 2 and 3. Composite metal oxides and carbon materials were sequentially disposed on the outer side of the iron-based phosphate, forming a multilayer composite structure of iron-based phosphate, composite metal oxide, and carbon material. After sintering, the metal oxides reacted with the highly active iron compounds remaining on the surface of the iron-based phosphate to generate composite metal oxides. On the one hand, this can convert the free iron on the surface of the iron-based phosphate into a composite metal oxide structure, reducing the dissolution of iron; on the other hand, it can also reduce the interfacial resistance of the iron-based phosphate and improve the electronic conductivity characteristics of the positive electrode active material.
[0090] The secondary batteries prepared in Examples 1-17 exhibit significantly improved cycle performance and resistance to iron dissolution without affecting the discharge capacity. The capacity retention (hereinafter also referred to as capacity retention) of the secondary batteries prepared in Examples 1-17 after 2000 cycles at 1C rate can reach over 90.1%; simultaneously, the iron migration can be controlled below 800 ppm.
[0091] Referring to Examples 10-15 and Comparative Example 1, although iron migration decreases with increasing metal oxide content, the discharge capacity also decreases. When the amount of composite metal oxide added is controlled between 1wt% and 5wt%, a balance can be achieved between iron migration and discharge capacity. That is, iron migration is reduced while maintaining a high discharge capacity.
[0092] Referring to Examples 1, 16-17, a decrease in carbon content increases M. x Fe y O δ Increasing the thickness reduces iron dissolution, but it will also decrease the discharge capacity. Increasing the carbon content will decrease M. x Fe y O δ The thickness of the material reduces the effect of iron dissolution and slightly decreases the discharge capacity.
[0093] The various implementations of this application have been described above. The foregoing description is exemplary and not exhaustive, nor is it limited to the disclosed implementations. Many modifications and variations will be apparent to those skilled in the art without departing from the scope and spirit of the described implementations. The terminology used herein is chosen to best explain the principles, practical applications, or improvements to technology in the market, or to enable others skilled in the art to understand the various implementations disclosed herein.
Claims
1. A positive electrode active material, characterized in that, The active particles comprise iron-based phosphates and composite metal oxides, wherein the composite metal oxides contain the chemical formula M. x Fe y O δ Compounds in which M includes metallic elements with an oxidation state greater than or equal to +2, 1≤x≤2, 1≤y≤2, 3≤δ≤6; The iron-based phosphate is connected to the composite metal oxide via POM covalent bonds.
2. The positive electrode active material according to claim 1, characterized in that, Based on the total mass of the active particles, the mass percentage of the composite metal oxide is 1wt% to 5wt%.
3. The positive electrode active material according to claim 1, characterized in that, M includes at least one of Al, Ti, Cr, Mn, Ga, Nb, Sn, Ta, and W.
4. The positive electrode active material according to claim 3, characterized in that, The ionic radius of the cation of M is 50 pm to 75 pm.
5. The positive electrode active material according to claim 3, characterized in that, The composite metal oxide includes at least one of the following compounds: Al2FeO4, TiFeO3, Cr2FeO4, MnFe2O4, Ga2FeO4, Nb2FeO6, SnFeO3, Ta2FeO6, and WFeO4.
6. The positive electrode active material according to claim 1, characterized in that, The crystal structure of the composite metal oxide includes at least one of spinel-type and perovskite-type structures.
7. The positive electrode active material according to claim 1, characterized in that, The iron-based phosphate includes the chemical formula Li u Fe 1-a D a Compounds of PO4, wherein 0.9 ≤ u < 1.1, 0 ≤ a < 1, and D is selected from at least one of Mn, Mg, Ti, V, Cr, Co, Ni, Cu, Zn, Al, Zr, and Nb.
8. The positive electrode active material according to claim 1, characterized in that, The positive electrode active material also includes carbon material, which is disposed on the outside of the active particles. Based on the total mass of the active particles, the mass percentage of the carbon material is 1wt% to 2.5wt%.
9. The positive electrode active material according to claim 8, characterized in that, The composite metal oxide is disposed at least partially on the outside of the iron-based phosphate, and the carbon material is disposed at least partially on the outside of the composite metal oxide.
10. The positive electrode active material according to claim 9, characterized in that, The composite metal oxide is disposed on the outer side of the iron-based phosphate with a thickness of 5~50 nm.
11. The positive electrode active material according to claim 9, characterized in that, The thickness of the carbon material is set to 8~40nm.
12. A secondary battery, characterized in that, It includes a positive electrode and a negative electrode, wherein the positive electrode includes a positive current collector and an active material layer disposed on at least one surface of the positive current collector, and the active material layer includes the positive active material according to any one of claims 1 to 11.
13. The secondary battery according to claim 12, characterized in that, In the cycle test of the secondary battery at an ambient temperature of 25°C and a voltage range of 2.5~3.65V, with constant current and constant voltage charging at 1C and constant current discharging at 1C, the iron migration amount after 2000 cycles is less than or equal to 1000ppm. The iron migration amount is the ratio of the mass of iron on the negative electrode to the mass of the positive electrode active material.
14. An electrical appliance, characterized in that, Includes the secondary battery according to claim 12 or 13, wherein the secondary battery serves as the power supply for the electrical equipment.